Effect of breeds on semen characteristics of aged bulls in the Indonesian National Artificial Insemination Center - Novianti, Irida; Purwantara, Bambang; Herwijanti, Enniek; Nugraha, Chairdin Dwi; Putri, Rafika Febriani; Furqon, Ahmad; Septian, Wike Andre; Rahayu, Sri; Nurgiartiningsih, Veronica Margareta Ani; Suyadi, Suyadi (Faculty of Animal Science, Universitas Brawijaya, 2020)
Madura and Bali cattle are two of Indonesian indigenous breeds. One possible method to increase their productivity is through artificial insemination (AI) using frozen semen. This study conducted at the Singosari National Artificial Insemination Center, East Java, Indonesia, to evaluate the semen characteristics of different bull breeds ranging in age from 7 to 10 years and to provide useful recommendations regarding the efficacy of older cattle. A total of 2016 ejaculation data recorded from Indonesian indigenous cattle (Madura and Bali bulls) and Bos taurus bulls (Simmental) were used in this study to analyze semen volume, sperm motility, and sperm concentration. Results revealed differences in semen volume, sperm motility, and sperm concentration among bull breeds (p < 0.05). Simmental bulls have the highest semen volume (p < 0.05) compared with Bali and Madura bulls. Base on sperm motility, Bali bulls showed the highest average value (p < 0.05) compared with Simmental and Madura bulls. Sperm concentration was the highest (p < 0.05) among Bali bulls compared with Simmental and Madura bulls. Another important finding was that the average semen volume, sperm motility, and sperm concentration of older bulls fulfilled the standard criteria established for frozen semen processing. Therefore, it would be possible to improve the performance of these breeds through artificial insemination using frozen semen of Madura and Bali bulls, which can be more widely distributed to farmers to increase their herd productivity. This study also indicates that Indonesian indigenous bulls have superior semen characteristics than Simmental bulls.